Study on Defensive Mechanism of Respiratory System - Quezada, Arnoldo (Highlights on Medicine and Medical Science Vol. 7, 2021)
The objective of this article is to describe the different components comprising the defense mechanisms of the respiratory system. The defense of the respiratory system comprises mechanical barrier phenomena, humoral factors and both cells of the innate immune response and of the specific adaptive immune response. The first line of lung defense corresponds to the barrier mechanisms and the innate immune response. Dendritic cells (DC) interact with pathogens and antigens by sending information to lymph nodes in the lung to generate an adaptive immune response. In this way, DCs link the innate response with the adaptive immune response. The adaptive immune response is specific through the production of antibodies and specific T lymphocytes, acting in a synergistic and coordinated way. In addition, immunological memory is generated. The knowledge of these mechanisms has made possible to modulate immune response by increasing protection mechanisms (eg. vaccines, immunostimulants) or reducing allergic, autoimmune phenomena or chronic inflammatory diseases of the respiratory system (eg. corticosteroids, biologics).